2014
DOI: 10.1167/iovs.13-13684
|View full text |Cite
|
Sign up to set email alerts
|

Rare Complement Factor H Variant Associated With Age-Related Macular Degeneration in the Amish

Abstract: Data from the cumulative genetic risk score analysis suggests that the variants reported by the AMDGene consortium account for a smaller genetic burden of disease in the Amish compared with the non-Amish Caucasian population. Using exome sequencing data, we identified a novel missense mutation that is shared among a densely affected nuclear Amish family and located in a gene that has been previously implicated in AMD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 33 publications
2
72
0
Order By: Relevance
“…None of the family members carried the rare AMD risk alleles at CFH R53C, CFH D90G, CFH P503A, or CFH R1210C [14][15][16]18 nor did they carry risk alleles for macular diseases in the BEST1, ABCA4, or other retinal degeneration-associated genes 25 . We measured serum FH levels in each family in order to assess the effects of the four CFH variants on secretion of the FH protein.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…None of the family members carried the rare AMD risk alleles at CFH R53C, CFH D90G, CFH P503A, or CFH R1210C [14][15][16]18 nor did they carry risk alleles for macular diseases in the BEST1, ABCA4, or other retinal degeneration-associated genes 25 . We measured serum FH levels in each family in order to assess the effects of the four CFH variants on secretion of the FH protein.…”
Section: Resultsmentioning
confidence: 96%
“…These two common variants explain 17% of AMD liability, but not everyone affected with AMD carries these variants 14 . Rare variants in CFH as well as other genes in the complement pathway have since been identified, and carry a higher risk of disease [14][15][16][17][18] . The CFH R53C variant, located in CCP1, decreases the ability of FH to perform decay accelerating activity 15 ; the CFH D90G variant, located in CCP2, was found to decrease cofactor-mediated inactivation 15 ; and the CFH R1210C variant, located in CCP20, shows defective binding of FH to C3d, C3b, heparin/glycosaminoglycans, and endothelial cells (Table 3) 14,30-33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Finland (Lim et al 2014), Iceland (Gudbjartsson et al 2015), Greenland (Moltke et al 2014), Sardinia (Scott et al 2007), and among the Old Order Amish (Pollin et al 2008;Hoffman et al 2014) have all demonstrated how populations with a history of recent bottlenecks display large variations in allele frequencies.…”
Section: Characteristics Of Isolated Populationsmentioning
confidence: 99%
“…Thanks to next generation sequencing techniques, we are beginning to accumulate a large catalog of low-frequency and rare variants (1000Genomes Project Consortium 2015UK10K Consortium 2015; Genome of the Netherlands Consortium, 2014), a few of which have already been implicated in complex traits (Cohen et al 2005;Shuldiner et al 2009;Cruchaga et al 2014;Flannick et al 2014;Hoffman et al 2014;Lange et al 2014;Santos-Cortez et al 2015;Krumm et al 2015;Surakka et al 2015). However, current study designs are not optimal for detecting association with rare variants.…”
Section: Introductionmentioning
confidence: 99%